PATTERN OF HOMICIDAL DEATHS IN FAISALABAD - Bashir, Muhammad Zahid; Saeed, Ahmad; Khan, Dilawar; Aslam, Muhammad; Iqbal, Javed; Ahmed, Mumtaz (Journal of Ayub Medical College Abbottabad, 2004)
Background: Homicide is a reflection of extreme aggression. Many factors influence such a behavior. Family environment, urbanization and the presence of weapons. We conducted this study on autopsies conducted at the department of forensic medicine, Punjab Medical College Faisalabad to know the dimensions of homicide in terms of age, sex, weapons involved and seasonal variation if any. Methods: The study encompasses all 188 cases of homicide reporting for autopsy at the department of forensic medicine, Punjab Medical College Faisalabad from July 2001 to June 2002.The cases were categorized on the basis of police inquest and autopsy findings. Results: The homicide rate in Faisalabad was 8.3/100,000population/year. The age of predilection was the third decade of life and males outnumbered females by a ratio of 3.47:1. A firearm was used in almost 50% of the cases. A surge in the summer months was noticed. Conclusion: Homicide rate is high inFaisalabad. Firearms are the major weapon used for committing homicide. Key Words: Homicide, Firearms, Autopsy.